Bahasa Inggris - Perdana, Andika Surya; Desyandri (Postgraduate, University of Mataram, 2023)
Learning that is still fixated on textbooks and which makes students unable to fully apply critical thinking skills is the background of this research. Therefore, the development of teaching materials for grade V elementary schools needs to be done using the Application Kvisoft Flipbook Maker with the PBL model. This research uses a type of development research or R&D using a design that refers to the ADDIE model with the following steps: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were class II students at SD Sambihisma 04, SDN 10 Ganting and SDN 48 Ganting, Koto Tangah District, Padang City with the results obtained from the validity standard analysis obtaining the criteria of